Nutritional status and sexual dimorphism in three amazonian caboclo communities - Pucciarelli, Hector Mario (2005)
Three Caboclo communities from Marajo Island (State of Pará, Brazil) were studied. Paricatuba is the most traditional one. Marajo-Açu is devoted to the extraction and commercialization of the fruit of açai. Praia Grande has adopted a mechanized agriculture, cattle raising and a cooperative religious organization. Three hundred and ten 0–30 year-old Caboclo males and females were measured. Each sample community was divided into three age stages: preadolescent (0–10 years old), youth (11–20 years old), and adult (21–30 years old). Body weight and height, mid upper-arm circumference, triceps skinfold, and bicondylar humerus width were measured. Body mass index, and upperarm fat, muscle and bone proportions were calculated. In preadolescents, underweight and stunting frequencies were found to be greater in Paricatuba and Marajo-Açu than in Praia Grande. Few significations for wasting were found in all. Sex dimorphism for youths was present in the three communities, whose upper-arm fat proportion was greater in females than in males. Adult Praia Grande males had a greater upper-arm muscle proportion – and females a greater upper-arm fat proportion – than in the other two villages. In synthesis, the three communities underwent some kind of nutritional stress, but Praia Grande was in better conditions than Paricatuba and Marajo-Açu. This suggests an improvement in Praia Grande quality of life, presumably due to westernisation.